The proposal for the implementation of elections in Indonesia: a framework based on the presidential system - Taufiq Yuli Purnama; Ramalina Ranaivo Mikea Manitra (Wacana Hukum, 2023)
As a democratic country, in order to promote the general welfare, all citizens have the same right to exercise their political rights. In the context of organizing general elections, a form of democracy adopted by Indonesia. . Elections that are carried out transparently and peacefully and the elected leaders are generated by the most votes, then the country can be called a democratic country. The purpose of this research is to show that the function of political parties in selecting legislative candidates  This type of research is normative legal research, using a conceptual approach. The research method is a legal scientific logic research procedure. The results of this study indicate that the application of an open proportional system has a major influence on every determination of the quality of legislative members, and the enactment of an open proportional system causes many popular legislative candidates to be elected without considering the capacity of the ability of legislative candidates who will ascend to office, and an open proportional system that best reflects the basic principles of democracy a In the implementation of several policies of t h e Constitutional Court with the Decision issued by allowing educational institutions as campaign sites. There are pros and cons to this. But basically where the community is smart in politics is one of the requirements in realizing a good democracy. The other main requirements are fair law enforcement and respect for human rights values.